The synthesis of novel crown ethers, part VII [1]. Coumarin derivatives of benzocrowns and cation binding from fluorescence spectra - (:unkn) unknown (SPRINGER, 2000)
4-[3-(1-benzopyran-2-one)] derivatives of benzo[12]crown-4, benzo[15]crown-5 and benzo-[18]crown-6 were synthesized from 4-[3-(1-benzopyran-2-one)]-1,2-dihydroxy-benzene reacting with bis-ethyleneglycol dihalides or pentaethylene glycol ditosylate in alkali carbonate/DMF/water. The original products were identified by high resolution EI-mass spectra as well as IR, H-1-NMR and C-13-NMR spectroscopy. The 1 : 1 binding constants of Mg2+, Li+, Na+ and K+ with the coumarin-benzocrowns were estimated using fluorescence emission spectroscopy in acetonitrile. The complexing enhanced quenching fluorescence spectra (CEQFS) and complexing enhanced fluorescence spectra (CEFS) exhibited the ion binding powers due to cationic recognition rules of the macrocycles.
Keywords: macrocycles; coumarins; cation binding; Mg2+; Li+; Na+; SUP; K+; fluorescence spectroscopy